MCNPX simulations of the SCANDAL setup for measurement of neutron scattering cross section at 175 MeV - Milan Tesinsky (2018)
The Scattered Nucleon Detection Assembly (SCANDAL) setup at The Svedberg Laboratory has been used to produce neutron elastic scattering cross section data at 175 MeV for bismuth and iron. This work presents MCNPX simulations of the experimental setup and aims to describe processes and data important for the upcoming off-line data analysis. In the experiment, neutrons scattered off the target are converted to protons, which are stopped in scintillator crystals. The results include a description of the proton spectra dependence on the neutron-to-proton conversion angle, suggesting a cut at a conversion angle of 15.2°. Calculation of the hit position gates indicates high proton leakage from the crystals. A study of the converter describes the role of its chemical composition and also the role of other plastic scintillators on the proton spectra. The neutron-to-proton conversion efficiency of the converter simulated by MCNPX is 5.1×10-4and corresponds to theoretical predictions. © 2010 The Royal Swedish Academy of Sciences.